(untitled) (Journal of the College of Basic Education, 2024)
The aesthetics achieved through excitement are linked to one of the important foundations in designing and producing the digital image to achieve multiple features that enhance the desires of the recipient. The element of excitement occupies an important place in the design of modern advertisements through the developments taking place in the modern world using computer technologies and the Internet. It is considered an important and main element that affects the recipient. The effect on advertising spaces and blocks may be distinct from others. Modern technology has added other important possibilities, such as illusion and three-dimensionality in designing and producing a digital image. After designing an image that was predominantly static, it has become due to digital technology that possesses multimedia properties in achieving aesthetic aspects in arousing the recipient through the use of the digital image. Including this. The current research emerged from the research problem through several questions, including the following: What are digital image processors and their effectiveness in achieving excitement and suspense? The importance of the current research was to organize the topic of digital image design and its relationship to excitement and suspense, and the role of globalization and modernity in influencing digital images and their repercussions on designers, those interested and specialists in this broad field, as well as benefiting from the capabilities related to the characteristics and their effectiveness among scholars and researchers in the field of modern digital design. . The current research aims to reveal the effectiveness of the digital image and the extent of its effectiveness in the recipient. The current research includes two sections, the first on the digital image in graphic design, and the second section on the effectiveness of the image and its impact on the recipient. In her research procedures, the researcher followed the descriptive approach to analyze the sample models represented by international advertisements that are compatible with the research path. Then she presented the conclusions of her research, the most important of which are: The digital image affects the recipient according to the intention of the designer and the purpose of the advertisement. The excitement is achieved through the designed exaggeration in the production of the digital image. The excitement in the digital image is linked to references. The recipient and the extent of his interaction with it. ​